Risk factors for newly-developed cardiovascular disease and quality of life during the COVID − 19 pandemic: an analysis of the English longitudinal study of ageing - Mubarak Patel; Olalekan Uthman (BMC, 2023)
Abstract Introduction The COVID-19 pandemic had a wide range of effects on the English population, including on health and quality of life due to the subsequent lockdown restrictions set. Aims To investigate longitudinal changes in developing cardiovascular disease (CVD) and how that affects quality of life from pre-pandemic and during two lockdowns in England, in adults aged 50 years and above, and what factors are associated with this. Methods Wave 9 of the core English Longitudinal Study of Ageing (ELSA) and Waves 1 and 2 of the ELSA COVID-19 sub-study were used to investigate the factors associated with developing CVD between timepoints, and what factors alongside CVD are associated with quality of life. Results Higher age and depression were associated with newly-developed CVD from pre-COVID to both COVID sub-study waves. Additionally, body mass index (BMI) increased odds of CVD and physical activity decreased odds. Non-White ethnicity, depression, females, and developing CVD were lower associated with quality of life. Decreased age and increased physical activity were associated with higher quality of life. Discussion Ethnicity was not associated with newly-developed CVD but was associated with quality of life. Other factors of importance include age, depression, gender, and physical activity. Findings are informative for future risk stratification and treatment strategies, especially while the COVID-19 pandemic is ongoing.